Determining the predictive impact of donor parity on the outcomes of human leukocyte antigen matched hematopoietic stem cell transplants: a retrospective, single-center study - Azari, Mojtaba; Barkhordar, Maryam; Bahri, Tanaz; Rad, Soroush; Kamranzadeh Fumani, Hosein; Mousavi, Seied Asadollah; Tavakoli Shiraji, Sahar; Azari, Morteza; Shafaroudi, Parisa; Vaezi, Mohammad (Frontiers in Oncology, 2024)
Donor choosing remains to play a pivotal role in allogeneic hematopoietic stem cell transplantation (allo-HSCT). Numerous criteria beyond HLA compatibility impact the selection of a suitable donor.We evaluated the effect of donor parity on transplant outcomes in a large homogeneously treated population that received an HLA-matched allo-HSCT between 2010 and 2021 at our center. All patients were transplanted from a peripheral blood stem cell source following a myeloablative Busulfan-based conditioning and the same protocol for graft-versus-host disease (GVHD) prophylaxis.A total of 1103 allo-HSCT recipients were included. 188 (17.04%) had transplants from parous female donors, whereas 621 (56.30%) and 294 (26.70%) received transplants from male and nulliparous female donors, respectively. HSCT from parous female donors compared to male and nulliparous females was associated with a significantly higher incidence of grade III-IV acute (a) GVHD (55.27% vs. 11.34 and 10.84%) and extensive chronic (c) GVHD (64.32% vs. 15.52 and 13.65%), as well as lower relapse incidence (RI).This study finds that while parous female donors are associated with higher incidences of grade III-IV aGVHD and extensive cGVHD, the advantages, such as a lower RI, outweigh the risks. The results of our study provide valuable insights for donor selection.